2016
DOI: 10.1364/boe.7.003882
|View full text |Cite
|
Sign up to set email alerts
|

Mental stress assessment using simultaneous measurement of EEG and fNIRS

Abstract: Previous studies reported mental stress as one of the major contributing factors leading to various diseases such as heart attack, depression and stroke. An accurate stress assessment method may thus be of importance to clinical intervention and disease prevention. We propose a joint independent component analysis (jICA) based approach to fuse simultaneous measurement of electroencephalography (EEG) and functional near-infrared spectroscopy (fNIRS) on the prefrontal cortex (PFC) as a means of stress assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
173
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(188 citation statements)
references
References 102 publications
12
173
1
2
Order By: Relevance
“…Under fusion of both modalities, the study reported 98% classification accuracy indicating that fNIRS and EEG modality complement each other in obtaining features that highly correlated with mental stress. This improvement is in line with our previous stress studies [21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: B Eegsupporting
confidence: 92%
“…Under fusion of both modalities, the study reported 98% classification accuracy indicating that fNIRS and EEG modality complement each other in obtaining features that highly correlated with mental stress. This improvement is in line with our previous stress studies [21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: B Eegsupporting
confidence: 92%
“…Experimental evidence that clinical depression involves hyperactivity in depressive circuit loops comes from a study by Mazarati et al, who found that when the level of neuronal excitability was experimentally increased by repeated subconvulsive stimulation of the brain, the laboratory animals began to demonstrate depressive-like behavior [23]. This observation, taken together with the observation that depressive symptoms in susceptible individuals commonly develop in association with the circuit-specific stimulatory effects of severe or recurrent psychosocial stress [117], is compelling evidence that clinical depression is a manifestation of hyperactivity in depressive brain circuitry. Lending further support to this hypothesis is the observation that the increased vulnerability to depression that is fueled by persistent psychosocial stress persists for about the same length of time as an experimentally-induced kindling effect [118].…”
Section: Experimental Evidencementioning
confidence: 99%
“…That is, many non-stressful epochs were wrongly identified as stressful epochs, limiting the utility of HRV in this context (55,56). Several recent studies have attempted to combine different physiological measures to improve the ability of an algorithm to identify stress states (24,25,29,33,(38)(39)(40)(41)(42). By combining select features from these physiological modalities using a support vector machine, we achieved high sensitivity (91%) and specificity (100%)-indeed more than that achieve using any independent measure alone (Supplementary Table 2).…”
Section: Identifying Stressful States and Non-stressful Statesmentioning
confidence: 99%
“…While biochemical assays are invasive, expensive, not amenable to continuous measurements, and vulnerable to diurnal cycles (18)(19)(20)(21), electrophysiological measures are non-invasive and more suitable for continuous monitoring. Measures like galvanic skin response (GSR) (22)(23)(24)(25)(26)(27)(28)(29), heart rate (HR) (24)(25)(26)28,30), heart rate variability (HRV) (27,31,32), and electroencephalography (EEG) (33)(34)(35)(36) are increasingly being used to assess stress response. The relationship between these physiological measures and stress response, and both state and trait anxiety, however, remains poorly understood (37).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation